Kemukjizatan Naẓm al-Qur’ān dalam Perspektif Syihāb al-Dīn al-Alūsī - Hilmy Muhammad (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2014)
This article explains the naẓm (structure) position as one of the main aspects of miracles of al-Qur’ān. It explains that although al-Qur’ānis in Arabic, but it does not use the form and composition of models that have been used by the Arabs in their works. Al-Qur’ān performs in different way, not in the form of poetry, rhyme, letter or speech, but in kalām (theword). The article then explains that the way to make sense of this kalām was used as a pioneering theory by ‘Abd al-Qāhir al-Jurjānī. This theory is then used and applied by al-Alūsī in his commentary book, Rūḥ al-Ma‘ānī. This study shows the importance of the naẓm of al-Qur’ān, in which it becomes specific guidelines for researcher to understand the message of the Qur’ān.Keywords: Qur’ānic miracles, naẓm, al-Alūsī.DOI: 10.15408/ref.v13i6.996